Characterization and fertility assessment of soils of Chandauli district of Eastern Uttar Pradesh for sustainable land use planning - SEEMA, SEEMA; GHOSH, A K; YADAV, SUNITA (The Indian Journal of Agricultural Sciences, 2020)
Seven typical pedons representing major landforms in semi-arid and sub-tropical ecosystem of Chandauli district of Uttar Pradesh, viz. plains, mid lands and uplands developed from alluvium parent material under varying land uses were studied for their morphological characteristics, physical and chemical properties and soil classification. The colour of the soils ranged from light brown grey to brownish yellow red with a dominant hue of 10YR. These soils were acidic to moderately alkaline (pH 4.8 to 8.4) in reaction, non-saline, moderately deep to very deep and had isohyperthermic temperature and udic soil moisture regime. Texture and total organic carbon (TOC) ranged from silty loam to silty clay loam and 0.1 to 29.7 kg/ha respectively. Soils were medium in phosphorus (6.8 to 24.2 kg/ha) and available potassium (159 to 376 kg/ha ). All the pedons had ochric epipedon and underlain by cambic horizon (P1 to P4) within the control section and as such they come under order Inceptisols, whereas profile 5 to profile 7 have argillic horizon so they come under order Alfisols. All soils of the study area fall in agricultural land under land capability classes III and IV having limitations of slope and erosion. On the basis of major soil constraints and potentials, suitable land use plan has been suggested.